การปรับปรุงระบบการจัดการพื้นที่ผลิต กรณีศึกษา โรงงานรีดพลาสติก พีวีซี - บัญชา ธาราสายทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The objective of this research is to improve shop floor management and control systems of a PVC sheet calendaring factory. The factory confronted with problems of delayed shipment and low production capability. The concept of shop floor management is implemented relating to production scheduling, dispatching, moves between cells, monitoring and controlling to this factory. Methodology for developing the shop floor management system is divided into 4 main parts: (1) collect setup-time data and considering a heuristic method for using in sequencing jobs for calendering process for an objective of set-up time minimization, (2) assigning responsibility and develop operation procedures for production dispatching and moves between cells rules using in shop floor for resources and information readiness preparation, (3) improve the procedure of production monitoring for instantly detect in problems occurred in shop floor and adjusting the collecting crucial data in production, and (4) implementing of production controlling system to prevent problems that may be occurred on shop floor and affect production plans. After the improvement process, the average monthly on-time shipment is increased from 60.39% to 75.65% and average monthly production efficiency is raised from 68.06% to 84.75%, respectively.